COVID-19 Infection and Prevention Knowledge, Attitude, and Practice Among Arabs in the Arab World and Abroad - Almutazballlah, Qablan; Nosaiba, Nosaiba; Moyasar, Al Tatari; Anas, Alnajjar; Esmanur, Elmasri; Abdallah, Khatatbeh; Furqan, Alfatlawi; Amal, Dawood; Lama, Alyousef; Asma, En-Naouaouy; Wafaa, Habbaba; Samah, Al Rifai; et al. (Journal of Biology and Life Science, 2023)
Humanity is currently living in one of its worst pandemics due to Coronavirus disease-19 (COVID-19). Measures to control this pandemic are affected by the people’s misinformation. This study aims to evaluate the global knowledge, attitudes, and practices (KAP) of the Arab population regarding COVID-19. Establish any connections between demographic information and the KAP of individuals. A descriptive cross-sectional survey was conducted for a period of 4 months from September to December 2021. A 24-question survey was randomly distributed in 16 different countries. Most of the participants (45.1%) were unsure whether the COVID-19 virus was man-made and released for political purposes. Only 39.6% of the participants believed the vaccine was safe (38.5% responded unsure, and 21.9% responded no). Reassuringly, most of the participants displayed a positive attitude towards the precautionary measures. Most of the study participants had high academic qualifications. Although most of the participants utilized reliable knowledge sources-certified governmental sources (41%) and the WHO and international scientific institutions (23.1%)-, there seems to be a sense of mistrust and uncertainty regarding the origin of the COVID-19 virus. This study identified major gaps in the knowledge of the Arabs which has negatively affected their attitude and practices when it comes to vaccination. More is to be done by authorities to reach the public to assure a proper source of knowledge.